2020
DOI: 10.1101/2020.03.17.20037689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing DAY-ZERO and Forecasting the Fade out of the COVID-19 Outbreak in Lombardy, Italy: A Compartmental Modelling and Numerical Optimization Approach

Abstract: Italy currently constitutes the epicenter of the novel coronavirus disease

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Consistent with our results, these studies have shown that rapid reopening of the economy without adequate testing and contact tracing could lead to a resurgence of the epidemic [14][15][16][17] . Specifically, they…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our results, these studies have shown that rapid reopening of the economy without adequate testing and contact tracing could lead to a resurgence of the epidemic [14][15][16][17] . Specifically, they…”
Section: Discussionsupporting
confidence: 92%
“…Other modeling studies have used SEIR-type compartmental models to assess the impact of social distancing, testing and contact tracing to curb the epidemic curve in Italy and the United Kingdom [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study states that, higher average temperature is potential candidate to limit the spread of COVID-19. Lucia Russo et al [14] presented a mechanism to find the first day of infections and predictions of COVID-19 in Italy. Depending upon proposed work, authors are able to estimate that the actual count of exposed cases of COVID-19.…”
Section: Related Workmentioning
confidence: 99%
“…Known models, statistical, mathematical, mechanistic space-state and empirical (machine learning) have been thoroughly reviewed recently 1 . Since the emergence of COVID-19, several newly published research articles rely on mathematical models to predict the spread of the virus, to estimate the basic reproduction factor, R 0 and, to highlight the influence of public policies on the outcome of the epidemic [2][3][4][5][6][7][8][9][10][11] . Statistical analyses of the epidemic data from different countries, by means of distribution and error functions, have also been performed with the aim of predicting the epidemic peak 12,13 some of which make use of machine learning techniques 14,15 .…”
Section: Introductionmentioning
confidence: 99%